A computerised identification key for 30 genera of plant parasitic nematodes - Bell, N.L. (New Zealand Plant Protection, 2002)
A computerbased key for identifying plant parasitic nematodes of temperate agriculture in New Zealand and around the world is described It uses the Lucid software developed at the University of Queensland and includes images of major diagnostic features The key is multiaccess rather than dichotomous so may be entered at any point allowing for the most obvious characters of a specimen to be scored first and thereby immediately reduce the number of likely taxa Both qualitative and quantitative characters are used The key requires that the specimen can be viewed microscopically but examples of most morphological terms are illustrated so the nonspecialist should be able to make use of the key